PERAN KELUARGA DAN SEKOLAH DALAM PENGEMBANGAN DAYA LENTING SISWA: UPAYA PROTEKSI ANAK DARI KEKERASAN - Sholicatun, Yulia (Universitas Ahmad Dahlan, 2010)
Recently, violence or bullying has become the customary phenomenon in society life. It´s included in education world whether by teacher to student and also among students. In the world of education, violence happens because of some factors either from the side of teacher, students or society. Violence can affect psychological aspect of students like anxiety, depression, lower students´ academic achievement, and lower students´ self esteem. Besides, tendency to develop of negative behaviors hence of an effort to enlarge their resilience ability is also extremely important. The involvement of school and parents role can be optimal to promote resilience. Protective potency along with school is juxtaposition development in school, existence of structuring and controlling and also developmental approach to curriculum that is supporting coping or problem solving and also self esteem. The role of parents and teachers in promoting resilience especially become a model from good moral reasoning either indoors or outdoors to students´ problems particularly which are related to problem of violence.